2020
DOI: 10.1111/tmi.13460
|View full text |Cite
|
Sign up to set email alerts
|

Spatial inequalities in skilled attendance at birth in Ghana: a multilevel analysis integrating health facility databases with household survey data

Abstract: Objective This study aimed at using survey data to predict skilled attendance at birth (SBA) across Ghana from healthcare quality and health facility accessibility. Methods Through a cross‐sectional, observational study, we used a random intercept mixed effects multilevel logistic modelling approach to estimate the odds of having SBA and then applied model estimates to spatial layers to assess the probability of SBA at high‐spatial resolution across Ghana. We combined data from the Demographic and Health Surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Travel time was chosen to model physical geographic access because it is a better measure that incorporates elevation, road network, and travel speed among other factors that influence geographic accessibility compared to network and straight-line distances [30]. Furthermore, we used AccessMod5.0 because it is free software, simple to use and widely used for analysing geographic accessibility to health services [21,31]. Travel times were modelled to two destinations, first to the nearest government health facility (i.e., public primary and secondary facilities, excluding dispensaries) then to FTHG (the major referral facility in Gombe) where all the cases and controls delivered their babies.…”
Section: Modelling Travel Time To Health Facilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Travel time was chosen to model physical geographic access because it is a better measure that incorporates elevation, road network, and travel speed among other factors that influence geographic accessibility compared to network and straight-line distances [30]. Furthermore, we used AccessMod5.0 because it is free software, simple to use and widely used for analysing geographic accessibility to health services [21,31]. Travel times were modelled to two destinations, first to the nearest government health facility (i.e., public primary and secondary facilities, excluding dispensaries) then to FTHG (the major referral facility in Gombe) where all the cases and controls delivered their babies.…”
Section: Modelling Travel Time To Health Facilitiesmentioning
confidence: 99%
“…Most studies focus on reporting stillbirth prevalence rates and exploring their clinical determinants [16][17][18][19]. Also, available studies investigated geographic accessibility factors known to strongly influence the use of skilled birth attendant and EmONC for pregnant women but not stillbirth outcome [20,21]. Furthermore, existing local stillbirth literature shows substantial regional disparity as they are mainly focused on southern Nigeria [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…We further contribute to the maternal and child health literature in Ghana by highlighting hotspots for unskilled birth attendance and the factors associated with such observations. Previous geospatial studies have focused on inadequate variables [ 21 ] or focused on skilled birth attendance [ 22 ]. Understanding the predictors of unskilled birth attendance and its geospatial coverage in Ghana is of high relevance to both local and public health understanding of unskilled birth attendance and highlight areas where national interventions will yield cost-effective results.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted at Nigeria con rms that Region was statistically signi cant factor that affected the use of skilled delivery [36]. A study by [37] posited different nding when they concluded that Region was not found to predict skilled attendance during delivery in their study in Ghana Using the 2008 Ghana Demographic and Health Survey. With reference to the occupation of the respondents, it was clear that women working in the clerical sector were two times more likely to utilize the services of nurses/midwives compared with those not working.…”
Section: Background Characteristics Of Respondentsmentioning
confidence: 99%
“…The study concluded that respondents from these places were more likely to utilize the services of Traditional birth attendants during birth delivery. In a study conducted to identify demographic, maternal and community predictors of skilled attendance at delivery among women, region was found to be associated with delivery assisted by traditional birth attendants [37].…”
Section: Background Characteristics Of Respondentsmentioning
confidence: 99%